Composite aerogel with hierarchical pore structure as well as preparation method and application of composite aerogel
By preparing a composite aerogel with multi-stage pore structure, the synergistic effects of Bletilla polysaccharide, Elosite and cellulose nanofibers were used to solve the problems of poor hemostasis and high cost of existing hemostasis materials, achieving efficient hemostasis, strong stability and good biocompatibility, and is suitable for industrial applications.
Patent Information
- Application Number
- CN202510714200.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-30
- Publication Date
- 2025-08-22
AI Technical Summary
The existing hemostatic materials have poor hemostatic effect, high cost, complex preparation process and difficult to debride, silicate powder is prone to residues, bacterial cellulose preparation cost is high, and industrial application is difficult.
Bletilla polysaccharide, elolite and cellulose nanofibers were used to prepare a composite aerogel with multi-stage porous structures through cross-linking reaction and freeze-drying treatment. Bletilla polysaccharide improved the adhesion and water absorption rate, elolite enhanced the mechanical properties and hemostatic effect, and cellulose nanofibers formed a porous structure to promote blood absorption.
It achieves efficient hemostasis, strong stability, good biocompatibility, simple preparation method and low cost, and is suitable for industrial applications.
Smart Images

Figure CN120514909A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a gel material, in particular to a composite aerogel with a multi-level pore structure, and also to a preparation method and application thereof, belonging to the technical field of external hemostatic dressings. Background Art
[0002] Excessive bleeding is one of the leading causes of death from trauma. The development of hemostatic materials that are fast, stable, safe, and easy to use is crucial for emergency trauma care, especially pre-hospital care for military combat injuries, traffic accidents, and natural disasters. Current hemostatic materials primarily include biological hemostatic agents such as thrombin and proteases, organic polymers such as polyethylene glycol, polyurethane, chitosan, and sodium alginate, and inorganic silicate mineral materials. Natural materials, due to their unique structure and properties, offer significant advantages in the hemostatic field. These include silicate minerals such as halloysite, kaolinite, and montmorillonite, nanofibers, chitosan, and porous starch, as well as traditional Chinese medicines such as Panax notoginseng and Bletilla striata. Natural silicate mineral materials offer advantages such as fast hemostasis, high stability, and high production yields. While direct application of silicate powder to wounds offers effective hemostasis, they are difficult to debride, prone to residue, and prone to inflammation. Mixing silicate powder with chitosan, sodium alginate, nanofibers, and other materials to prepare hemostatic sponges and hydrogels, or blending with spinning solutions to prepare hemostatic fiber membranes, has been a recent trend. However, the raw materials for hemostatic hydrogels and electrospun fiber membranes are expensive, and their poor compatibility with silicate powders results in a low silicate powder dosage, which in turn affects hemostatic performance.
[0003] The literature (“Bacterial cellulose kaolin nanocomposites for application as biomedical wound healing materials”, Dwi Wanna et al, 《 adv. Nat. Scinanosci. nanotechnol》 , 2013(4), 045002m, 20130814) discloses a bacterial cellulose / kaolin composite material, the negatively charged areas on the surface of which can accelerate the blood coagulation process by binding to coagulation factor XII. However, the preparation cost of the bacterial cellulose is high, which is not conducive to large-scale production.
[0004] Patent publication number CN115433371A provides a method for preparing a hemostatic hydrogel containing natural polysaccharides, comprising the following steps: (1) preparing a natural polysaccharide-clay aqueous solution: adding polyphenols and natural polysaccharides to the clay aqueous solution under stirring, and adjusting the pH value of the system to 8-9 to form a natural polysaccharide-clay aqueous solution; (2) preparing a hydrogel: adding monomers, an initiator, and a cross-linking agent to the natural polysaccharide-clay aqueous solution to form a mixed solution, stirring the solution uniformly, and reacting the solution at 10-40°C for 10-60 minutes to obtain the hemostatic hydrogel containing natural polysaccharides. However, the preparation process is complicated and costly, making it unsuitable for industrial application. Summary of the Invention
[0005] In order to achieve the above technical objectives, the present invention provides a composite aerogel with a hierarchical pore structure. A composite aerogel with a hierarchical pore structure is prepared from raw materials containing bletilla striata polysaccharide, halloysite and cellulose nanofibers through cross-linking reaction and freeze-drying treatment, wherein the mass ratio of the bletilla striata polysaccharide, halloysite and cellulose nanofibers is (0.002~0.02):0.1:(0.1~0.3).
[0006] The present invention significantly improves the hemostatic, mechanical, and stability properties of the gel material through the synergistic effects of bletilla polysaccharide, halloysite, and cellulose nanofibers. The insertion of hard halloysite into the soft nanocellulose gel improves the mechanical properties of the aerogel, while also enhancing its hemostatic properties and resolving the problem of clay powder residue. The addition of sticky bletilla polysaccharide into the halloysite / cellulose nanofiber gel improves the aerogel's cohesiveness, making it less likely to disperse, while also increasing its water absorption and promoting hemostasis. Cellulose nanofibers cross-link with aluminum ions to form a porous aerogel. The aerogel's multi-level pore structure promotes rapid absorption of blood from the bloodstream, as well as contact with active substances such as platelets, red blood cells, and coagulation factors, accelerating hemostasis.
[0007] As a preferred solution, the mass ratio of the bletilla striata polysaccharide, halloysite and cellulose nanofiber is (0.01-0.02):0.1:(0.1-0.3).
[0008] As a preferred solution, the Bletilla striata polysaccharide is extracted from the traditional Chinese medicine Bletilla striata. Bletilla striata polysaccharide has natural hemostatic effect and good adhesion and water absorption, and can also cause platelet aggregation and adhesion to promote blood coagulation.
[0009] As a preferred embodiment, the halloysite is a halloysite nanotube powder. Halloysite's tubular structure and fine surface pores give it excellent adsorption properties. It selectively absorbs water from the blood, effectively concentrating coagulant-active substances and promoting platelet aggregation and adhesion. Its negatively charged surface also stimulates coagulation factors, initiating the intrinsic coagulation pathway and achieving coagulation. Furthermore, halloysite does not cause thermal damage during hemostasis.
[0010] As a preferred solution, the tube diameter of the halloysite is 30-70 nm, and the tube length is 1-3 μm.
[0011] As a preferred solution, the cellulose nanofibers are produced by TEMPO oxidation. TEMPO-oxidized cellulose nanofibers have carboxyl groups, which promote the activation of coagulation reactions and platelet aggregation. Furthermore, the cellulose nanofibers have a small diameter and a high aspect ratio, allowing them to form a porous aerogel membrane structure, thereby enhancing water absorption.
[0012] As a preferred solution, the carboxyl content in the cellulose nanofibers is 1.2-3.0 mmol / g.
[0013] As a preferred solution, the cellulose nanofibers have a length of 1 to 3 μm and a diameter of 5 to 20 nm.
[0014] The present invention also provides a method for preparing a composite aerogel with a multi-level porous structure, which comprises adding a crosslinking agent to a mixed solution containing bletilla striata polysaccharide, halloysite and cellulose nanofibers to carry out a crosslinking reaction, obtaining a gel and then freeze-drying the gel.
[0015] The present invention uses a cross-linking-freeze-thaw method to obtain a three-dimensional porous aerogel with rich pores, which can greatly improve the hemostatic properties of the material and enhance its stability. At the same time, freeze-drying can also be used to obtain a larger pore size structure.
[0016] As a preferred solution, the cross-linking agent includes at least one of aluminum salt, calcium salt, and iron salt.
[0017] As a preferred embodiment, the aluminum salt is aluminum chloride.
[0018] As a preferred solution, the molar ratio of the cross-linking agent to the Bletilla striata polysaccharide is 2.5-12:0.5-12.
[0019] As a preferred solution, the cross-linking agent is introduced in the form of a solution with a concentration of 0.001-0.2 mol / L.
[0020] As a preferred solution, the cross-linking agent is added in two times, and the molar amount of the first addition is 2 to 42 times that of the second addition.
[0021] As a preferred solution, the concentration of the aluminum chloride solution added for the first time is 0.05-0.15 mol / L.
[0022] As a preferred solution, the concentration of the aluminum chloride solution added for the second time is 0.005-0.015 mol / L.
[0023] As a preferred solution, the conditions of the cross-linking reaction are: temperature of 20-40° C. and time of 20-30 h.
[0024] As a preferred solution, the freeze-drying conditions are: temperature of -70°C to -20°C, and time of 24 to 55 hours.
[0025] As a preferred solution, the mixed solution containing Bletilla striata polysaccharide, halloysite and cellulose nanofibers is prepared by mixing nanocellulose aqueous dispersion, water, halloysite and Bletilla striata polysaccharide solution.
[0026] As a preferred solution, the mass concentration of the nanocellulose aqueous dispersion is 0.6-1.5%.
[0027] As a preferred solution, the concentration of the Bletilla striata polysaccharide solution is 0.0001~0.001g / mL.
[0028] As a preferred solution, after freeze drying, an alcohol solvent is used for thawing, preferably a mixed solvent of ethanol and isopropanol.
[0029] The present invention also provides an application of a composite aerogel with a multi-level pore structure as a hemostatic dressing. The composite aerogel can effectively improve the hemostatic effect, has stable performance, good biocompatibility, and almost no side effects.
[0030] Compared with the prior art, the present invention has the following beneficial effects: (1) The composite aerogel has excellent hemostatic properties, strong stability, and good biocompatibility, and can be effectively used in hemostatic dressings; (2) The preparation method is simple, low-cost, and suitable for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are merely embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.
[0032] Figure 1 This is a microscopic morphology of the composite aerogel prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0033] The following will clearly and completely describe the technical solutions of the present invention in conjunction with the embodiments of the present invention and the accompanying drawings. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0034] The batch number of the bletilla striata polysaccharide product used in the present invention is PBC210406001, which was purchased from Shaanxi Panier Biotechnology Co., Ltd., and the halloysite used has a CAS number of 1332-58-7, which was purchased from Sigma-Aldrich.
[0035] The cellulose nanofibers used in the present invention have a solid content of 1% and are purchased from Shansi Technology.
[0036] Example 1
[0037] The following are the steps for preparing a composite aerogel with a multi-level porous structure:
[0038] 20 g of a 1% TEMPO-oxidized nanocellulose aqueous dispersion was weighed and diluted with water to a 0.6% concentration. 0.1 g of halloysite powder and 20 mL of a 0.0001 g / mL Bletilla striata polysaccharide solution were then added and stirred for 2 hours to produce a Bletilla striata polysaccharide / halloysite / cellulose mixture. To this mixture was then added 100 mL of a 0.1 mol / L AlCl₃ solution. After standing for 1 hour to form a gel, the remaining liquid was discarded and 100 mL of a 0.01 mol / L AlCl₃ solution was added. The mixture was shaken at 30°C for 24 hours. Finally, the shaken sample was removed and placed in a cryogenic freezer at -60°C for 48 hours. It was then thawed at room temperature four times by adding 95 mL of anhydrous ethanol and 5 mL of isopropanol. After thawing, the mixture was vacuum-dried for 1 day to obtain a hemostatic composite aerogel, labeled 1% BSP / HNTs / TOCNs.
[0039] Example 2
[0040] The composite aerogel was prepared by the method of Example 1, except that the concentration of the Bletilla striata polysaccharide solution was 0.0005 g / mL, and the prepared composite aerogel sample was labeled as 5% BSP / HNTs / TOCNs.
[0041] The micromorphology of the aerogel prepared under the conditions of this embodiment was analyzed using a scanning electron microscope. Figure 1 As shown in the figure, it can be seen that the composite aerogel has a porous structure, tubular halloysite is embedded in the membrane or attached to the membrane surface, and the Bletilla striata polysaccharide is colloidally mixed with halloysite and nanocellulose.
[0042] Example 3
[0043] The composite aerogel was prepared by the method of Example 1, except that the concentration of the Bletilla striata polysaccharide solution was 0.001 g / mL, and the prepared composite aerogel sample was labeled as 10% BSP / HNTs / TOCNs.
[0044] Example 4
[0045] Composite aerogels were prepared by the method of Example 2, except that the mass content of the TEMPO-oxidized nanocellulose aqueous dispersion was controlled to 1%, and no water was added for dilution. The prepared composite aerogel sample was labeled BSP / HNTs / 1%TOCNs.
[0046] Example 5
[0047] Composite aerogels were prepared by the method of Example 2, except that the mass content of the TEMPO-oxidized nanocellulose aqueous dispersion was controlled to 1.5% and no water was added for dilution. The prepared composite aerogel sample was labeled BSP / HNTs / 1.5%TOCNs.
[0048] Comparative Example 1
[0049] The composite aerogel was prepared by the method of Example 1, except that the Bletilla striata polysaccharide solution was not added, and the prepared gel sample was labeled HNTs / TOCNs.
[0050] The samples of each embodiment and comparative example were subjected to an in vitro coagulation test, and the steps were as follows:
[0051] A 10mg sample was weighed and placed in a test tube. 400µL of New Zealand rabbit whole blood, pre-warmed at 37°C, was added. Then, 40µL of 0.2M CaCl2 solution was quickly added to initiate the coagulation process. The timer was immediately started and the flow of blood in the centrifuge tube was observed. The timer was stopped until the blood stopped flowing. This was the in vitro coagulation time. Each sample was repeated five times, with a group without sample added serving as a blank control. The test results are shown in Table 1.
[0052]
[0053] As can be seen from Table 1, the Bletilla striata polysaccharide / halloysite / nanocellulose composite aerogel prepared in the present invention has a rapid coagulation function, and the coagulation effect is significantly better than that of the blank control group and Comparative Example 1. In addition, the hemostatic efficacy of the composite gel can be adjusted by adjusting the mass ratio of Bletilla striata polysaccharide, nanocellulose, and halloysite. When the mass ratio of Bletilla striata polysaccharide, halloysite, and nanocellulose is 0.01:0.1:0.2 (Example 2), the coagulation time is the shortest and the coagulation effect is the best.
[0054] The gel materials prepared in each embodiment and comparative example were subjected to an in vitro coagulation index test, and the steps were as follows:
[0055] 5 mg of sample was added to each 6-well plate, followed by the addition of 200 µL of New Zealand rabbit anticoagulated whole blood and 20 µL of 0.2 M CaCl2 solution. After the 6-well plate was incubated in a thermostatic bath for a certain period of time, distilled water was slowly injected, taking care to avoid direct impact on the blood clot to prevent damage to the clot structure. The supernatant was then centrifuged. After centrifugation, the absorbance value was measured at a wavelength of 540 nm using a spectrophotometer. The coagulation index (BCI) (%) = A 样品 / A 空白 ×100%, test results are shown in Table 2.
[0056]
[0057] It can also be seen from Table 2 that the Bletilla striata polysaccharide / halloysite / nanocellulose composite aerogel prepared in the present invention has a rapid coagulation function, and the coagulation effect is significantly better than that of the blank control group and comparative example 1.
[0058] The hemolysis rate test was performed on the products of Example 2 and Comparative Example 1 of the present invention, and the steps were as follows:
[0059] Take 2 mL of normal saline, add the samples of Example 2 and Comparative Example 1, respectively, to prepare suspensions with concentrations of 1 mg / mL, 3 mg / mL, and 5 mg / mL, respectively, and then add 2 mL of 2% red blood cell suspension. Each mixed system was placed in a 37°C constant temperature water bath and incubated for 1 hour, then centrifuged at 3000 rpm for 10 minutes, and the supernatant was collected. The absorbance of the supernatant at a wavelength of 540 nm was measured using a spectrophotometer. Each sample was repeated 3 times, and the hemolysis rate of each sample was calculated. The results are shown in Table 3. The hemolysis rate is calculated as follows: Hemolysis rate (%) = (A 样品 -A 阴性 ) / (A 阳性 -A 阴性 )×100%.
[0060]
[0061] As can be seen from Table 3, the hemolysis rates of the composite aerogels prepared in the present invention are all lower than 5%, and the hemolysis rates are significantly lower than that of Comparative Example 1, indicating that the composite aerogels of the present invention have excellent blood compatibility and safety.
[0062] The porosity test was performed on each embodiment of the present invention and the comparative example, and the steps were as follows:
[0063] Fill a 25 mL beaker with ethanol and weigh it as M1. After pouring out some of the ethanol, put in a sample weighing M. After the sample is filled with ethanol, replenish the ethanol and weigh it as M2. Take out the sample and weigh the remaining ethanol and beaker again as M3. Repeat three times for each sample. The porosity (P) is calculated according to the following formula P = (M2-M-M3) / (M1-M3) × 100%.
[0064] The water absorption rate of each embodiment of the present invention and the comparative example was tested in the following steps:
[0065] Weigh the dry sample (denoted as W1) and add water dropwise using a rubber-tipped dropper until fully absorbed. After 15 minutes without change, remove the excess water. Weigh the sample after full absorption (denoted as W2) and calculate the water absorption rate. Repeat this process three times for each sample. Water absorption rate (%) = (W2 - W1) / W1 × 100%. Porosity and water absorption test results are shown in Table 4.
[0066]
[0067] As can be seen from Table 4, the composite aerogel material prepared in the present invention has rich porosity and high water absorption, which is beneficial to improving the coagulation effect.
[0068] Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the present invention is not limited to the embodiments shown herein, but is to be construed in the widest manner consistent with the principles and novel features disclosed herein.
Claims
1. A composite aerogel with a hierarchical pore structure, characterized in that: The invention is prepared from raw materials containing bletilla striata polysaccharide, halloysite and cellulose nanofiber through cross-linking reaction and freeze-drying treatment. The mass ratio of the bletilla striata polysaccharide, halloysite and cellulose nanofiber is (0.002-0.02):0.1:(0.1-0.3).
2. The composite aerogel with a multi-level porous structure according to claim 1, characterized in that: The halloysite is halloysite nanotube powder; The tube diameter of the halloysite is 30-70 nm, and the tube length is 1-3 μm.
3. The composite aerogel with a multi-level porous structure according to claim 1 or 2, characterized in that: The cellulose nanofibers are prepared by TEMPO oxidation method; The carboxyl content of the cellulose nanofibers is 1.2-3.0 mmol / g.
4. The method for preparing a composite aerogel with a hierarchical pore structure according to any one of claims 1 to 3, characterized in that: A cross-linking agent is added to a mixed solution containing bletilla striata polysaccharide, halloysite and cellulose nanofibers to carry out a cross-linking reaction, and then a gel is obtained by freeze-drying.
5. The method for preparing a composite aerogel with a multi-level porous structure according to claim 4, characterized in that: The cross-linking agent includes at least one of aluminum salt, calcium salt and iron salt; The molar ratio of the cross-linking agent to the bletilla striata polysaccharide is 2.5-12:0.5-12.
6. The method for preparing a composite aerogel with a multi-level porous structure according to claim 4 or 5, characterized in that: The cross-linking agent is added in two times, and the molar amount of the first addition is 2 to 42 times that of the second addition.
7. The method for preparing a composite aerogel with a multi-level porous structure according to claim 4, characterized in that: The conditions of the cross-linking reaction are: temperature of 20-40°C and time of 20-30h; The freeze-drying conditions are: temperature of -70°C to -20°C, and time of 24 to 55 hours.
8. The method for preparing a composite aerogel with a multi-level porous structure according to claim 4, characterized in that: The mixed liquid containing bletilla striata polysaccharide, halloysite and cellulose nanofiber is prepared by mixing nanocellulose aqueous dispersion, halloysite and bletilla striata polysaccharide solution.
9. The method for preparing a composite aerogel with a hierarchical pore structure according to claim 8, characterized in that: The mass concentration of the nanocellulose aqueous dispersion is 0.6-1.5%; The concentration of the bletilla striata polysaccharide solution is 0.0001-0.001 g / mL.
10. Use of a composite aerogel with a multi-level porous structure according to any one of claims 1 to 3, characterized in that: As a hemostatic dressing.
Citation Information
Patent Citations
Preparation method of hemostatic hydrogel containing natural polysaccharide
CN115433371A